When can I hold my baby? An audit of time to first cuddle for preterm babies (<32 weeks) pre introduction and post introduction of a Family‐Integrated Care model. Issue 23 (12th May 2021) - Murdoch, Jamee; Hauck, Yvonne; Aydon, Laurene; Sharp, Mary; Zimmer, Margo
Abstract: Aim: The audit examined time to first cuddle between preterm babies (born < 32 weeks) and their parent pre‐ and post‐introduction of a family‐integrated care model. Secondary outcomes included time to full feeds and length of neonatal intensive care stay. Background: Parental separation due to neonatal intensive care unit admission is known to negatively affect parental and baby wellbeing. Design: A "before‐after" design compared outcomes for babies admitted pre‐ (2015) and post (2018)‐implementation of the model in a Western Australian neonatal intensive care unit. Methods: A retrospective medical record audit included babies from two gestational age groups in 2015 and 2018, born ≤27 + 6 weeks and 28–31 + 6 weeks. SQUIRE checklist guided reporting of the audit. Results: One hundred fifty‐three babies were included in the audit, 79 from 2015 (≤27 + 6 weeks n  = 39 and 28–31 + 6 weeks n  = 40) and 74 from 2018 (≤27 + 6 weeks n  = 35 and 28–31 + 6 weeks n  = 39). Babies in both years were born at similar median gestational ages with comparable birthweights. Babies born ≤27 + 6 weeks in 2018 were cuddled earlier (median = 141 h old) compared with those in 2015 (median = 157 h old). Median time to reach full feeds decreased and was significant in the ≤27 + 6‐week group: 288 h (12 days) in 2015 to 207.5 h (8.6 days) in 2018. Length of stay was longer for the ≤27 + 6‐week gestation 2018 group (median = 64 days) and 28–31 + 6‐week gestation 2018 group (median = 22 days). Conclusion: Family‐integrated care models may decrease the time to first cuddle and full feeds. Further research on outcomes such as breastfeeding, infant weight gain and length of stay can extend existing knowledge. Relevance to clinical practice: Family‐integrated care models may offer benefits to families of hospitalised preterm babies and investigating barriers to its implementation and creation of solutions to overcome barriers warrants attention.